Peran Kepuasan dalam Memediasi Fitur Layanan dan Penerimaan Teknologi Mobile Banking BNI Terhadap Loyalitas Nasabah - Dewi, Christina Ayu Maha; Sanica, I Gede (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
The development of the digital world, especially from the financial technology sector, is proliferating. This is due to the high public interest in adopting information technology in all aspects of life to support daily activities. This study analyses customer satisfaction and loyalty in accepting BNI mobile banking application technology. The Technology Acceptance Model is the subject of this research. Location This research was conducted in Denpasar City, Bali Province. This type of research is quantitative by using the BNI mobile banking community in Denpasar City as a sample taken using the quota sampling technique. Data from 157 respondents were obtained by distributing open questionnaires with an interval scale of 1 to 10 points. Data analysis in this study used SEM through the PLS approach with the SmartPLS 3.2 program. The study results show that the TAM model's independent variables, namely perceived convenience and perceived benefits, can have a significant and positive effect partially on customer loyalty and through the intervening variables on customer satisfaction. Other results stated that the service feature variable did not affect customer satisfaction directly or customer loyalty through customer satisfaction. Future research is expected to add other TAM internal variables to strengthen research on technology acceptance